Decoupling as a Mechanism of Change in Mindfulness and Acceptance: A Literature Review. (November 2015) - Levin, Michael E.; Luoma, Jason B.; Haeger, Jack A.
A growing body of research within the acceptance and mindfulness-based therapies suggests that these treatments may function in part by reducing or eliminating (i.e., decoupling) the normative relationships between internal experiences and other internal/overt behavior. Examples of decoupling effects found in this review include reduced relationships between urges to smoke and smoking behavior, between dysphoric mood and depressive cognitions, and between pain intensity and persistence in a painful task. A literature review identified 44 studies on acceptance and mindfulness that demonstrated decoupling effects. Overall, preliminary evidence for decoupling effects were found across a broad range of problem areas, including substance abuse, depression, eating disorders, overeating, chronic pain, anxiety, relationships, anger, avoidance behavior, and self-harm, with the strongest evidence currently available in the area of substance abuse. However, the review also notes a general lack of replication studies on decoupling effects and the need for more well-powered and controlled research testing specific decoupling hypotheses.